THE INFLUENCE OF WORK-LIFE BALANCE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN WORK FROM HOME - Supriyatin Sy (INFOKUM, 2023)
This research aims to test and expand upon existing literature concerning the effect of workplace discipline on employee performance. Based on this description, the purpose of this study is to investigate the impact of work-life balance and work discipline on employee performance while working from home. This research comprises quantitative investigation of causal links between variables by evaluating hypotheses. Employees from Investment and One Stop Service compose the sample for this study. The SmartPls software is used for path analysis in data analysis. In addition, a Different Test utilizing One-Way ANOVA was conducted to examine differences in work-life balance, work discipline, and performance between WFH and WFO personnel. The results of the study indicate that work life balance has a positive and substantial effect on employee performance, and that work discipline has a positive and significant effect on employee performance. There is a considerable difference between WFH and WFO employees in terms of work-life balance, but there is no significant difference in terms of work discipline and performance.